PIXE‐alpha non‐destructive and in situ compositional investigation of black gloss on ancient pottery. (4th May 2016) - Pappalardo, L.; Barresi, S.; Biondi, G.; Caliri, C.; Caruso, F.; Catalano, R.; Lamagna, G.; Manenti, G. A.; Monterosso, G.; Orlando, A.; Rizzo, F.; Romano, F.P.; et al.
Abstract : The chemical characterization of the black gloss on ancient pottery is, since several years, the object of different scientific investigations. Among the different typologies of black gloss, the Attic one is the most refined, because it is prepared by using a fine suspension of an illitic clay applied on the surface of the clay body so that, after an oxiding‐reducing‐oxiding firing cycle at high temperature (800–950 °C), it reaches the typical shiny black aspect. Red figure vases were largely produced in South Italy often reaching a high artistic level. This is the case of the Sicilian red figure vases, sometimes called 'Sicelioti', whose production began in Sicily around the end of the fifth centuryBC and continued until the beginning of the third centuryBC . The aim of this work is to submit and compare a selection of data related to the chemical composition of the surface black gloss of some Attic and Sicilian red figure vases: This has been investigated, and a chemical‐based discrimination has been proposed. The non‐destructive particle‐induced X‐ray emission‐alpha portable spectrometer was used. The results, carried out in situ at the 'Paolo Orsi' Archaeological Museum in Syracuse (Sicily), together with the ones recently obtained in similar analyses at the Archaeological Museum of Catania University, confirmed the compositional stability of Attic vase black gloss and indicated that in a well‐defined time period, the chemical composition of the Sicilian black gloss decorations is very stable and superimposable with that of the contemporary Attic artifacts. Copyright © 2016 John Wiley & Sons, Ltd.